Reactions to research on sex differences: Effect of sex favoured, researcher sex, and importance of sex-difference domain. - Andrew Thomas (British Journal of Psychology, 2022)
Two studies (total N = 778) looked at (1) how people react to research finding a sex difference depending on whether the research puts men or women in a better light and (2) how well people can predict the average man and average woman's reactions. Participants read a fictional popular-science article about fictional research finding either a male- or a female-favouring sex difference. The research was credited to either a male or a female lead researcher. In both studies, both sexes reacted less positively to differences favouring males; in contrast to our earlier research, however, the effect was larger among female participants. Contrary to a widespread expectation, participants did not react less positively to research led by a female. Participants did react less positively, though, to research led by a male when the research reported a male-favouring difference in a highly valued trait. Participants judged male-favouring research to be lower in quality than female-favouring research, apparently in large part because they saw the former as more harmful. In both studies, participants predicted that the average man and woman would exhibit substantial own-sex favouritism, with both sexes predicting more own-sex favouritism from the other sex than the other sex predicted from itself. In making these predictions, participants overestimated women's own-sex favouritism, and got the direction of the effect wrong for men. A greater understanding of the tendency to overestimate gender-ingroup bias could help quell antagonisms between the sexes.